Simplify each expression, and then arrange them in increasing order based on the coefficient of n2. -5(n3 – n2 – 1) + n(n2 – n) (n2 – 1)(n + 2) – n2(n – 3) n2(n – 4) + 5n3 – 6 2n(n2 – 2n – 1) + 3n2
![Simplify each expression and then arrange them in increasing order based on the coefficient of n2 5n3 n2 1 nn2 n n2 1n 2 n2n 3 n2n 4 5n3 6 2nn2 2n 1 3n2 class=](https://us-static.z-dn.net/files/dac/73baac78e6378ce62255f6b5e7433111.png)
Answer:
Step-by-step explanation:
-5(n^3 - n^2 - 1) + n(n^2 - n)
-5n^3 + 5n^2 + 5 + n^3 - n^2
-4n^3 + 4n^2 + 5 <===
(n^2 - 1)(n + 2) - n^2(n - 3)
n^2(n + 2) - 1(n + 2) - n^3 + 3n^2
n^3 + 2n^2 - n - 2 - n^3 + 3n^2
5n^2 - n - 2 <===
n^2(n - 4) + 5n3 - 6
n^3 - 4n^2 + 5n^3 - 6
6n^3 - 4n^2 - 6 <===
2n(n^2 - 2n - 1) + 3n^2
2n^3 - 4n^2 - 2n + 3n^2
2n^3 -n^2 - 2n <===
putting them in order based on the coefficient n^2 is :
6n^3 - 4n^2 - 6
2n^3 - n^2 - 2n
-4n^3 + 4n^2 + 5
5n^2 - n - 2